TINJAUAN TENTANG PARTISIPASI MASYARAKAT DALAM MENDUKUNG PEMBANGUNAN DESA MEMAHAK TEBOQ KABUPATEN MAHAKAM ULU - F.Theresia Soong (ADMINISTRASI PUBLIK, 2020)
This research is motivated by community participation in participation in building their villages, both in the participation of the mind, participation of personnel, participation in expertise, participation in goods and participation in money.The purpose of this research is to find out how community participation in the implementation of regional development in Mamahak Teboq Village, Mahakam Ulu Regency. The type of research or explanation used is descriptive qualitative used to describe research variables. Types of data used are observation, interviews, and documentation.By carrying out research in the Mamahak Teboq village, Mahakam Ulu Regency, it is hoped that it can give an idea of how community participation in the implementation of regional development so that the participatory development concept that has been applied can be measured and can be used as a reference in further research related to the substance of the discussion.From the results of the research that has been carried out, it can be illustrated that the implementation of participatory development in the Mamahak Teboq village when referring to the results of the musrenbang that have been recorded in the Bappeda of Mahakam Ulu Regency, the results obtained are that although in the planning stage the community continues to participate, but at the stage of implementation of community participation which was expected to exist, apparently was not found at all, because at the project implementation stage it was carried out by the winning contractor. However, if we refer to the development projects implemented by the empowerment program that runs in the Mamahak Teboq village, mainly funded from village allocation funds, the research found that the enthusiasm of the community to participate in each stage of development carried out starting at the planning, implementation, until the project evaluation stage was very high. This can be concluded in the implementation stage there are still many things that must be addressed.